2013
DOI: 10.1111/j.1559-1816.2012.00991.x
|View full text |Cite
|
Sign up to set email alerts
|

How immigrant adolescents' self‐views in school and family context relate to academic success in Germany

Abstract: Immigrants' sense of self can be derived both from being members of their ethnic in‐group and their country of residence. We examined how the ways in which immigrant adolescents integrate these self‐views in relation to academic success in German schools. Students describe themselves at school and when with family. Using a standardized literacy performance test, analyses revealed that immigrants whose school‐related self‐view did not include Germany were less successful: Students who described their self as in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 45 publications
(91 reference statements)
3
25
0
6
Order By: Relevance
“…In contrast, in recent studies from Germany, only cultural minority youths' mainstream identity was associated with school achievement (Schotte, Stanat, and Edele 2017;Hannover et al 2013; Schachner, van de Vijver, and Noack 2018), whereas both heritage and mainstream identity were associated with psychological adjustment, including higher life satisfaction and reduced problem behaviour (Schotte, Stanat, and Edele 2017;Schachner, van de Vijver, and Noack 2018). Some authors have argued that the German school context might hold particularly high assimilative pressures, where students are expected to adapt to the mainstream culture while neglecting their heritage culture (Hannover et al 2013;Bender-Szymanski 2012). Therefore, in an assimilative school context, emphasising mainstream identity might be more important for school success than heritage identity (Makarova and Birman 2016;Schotte, Stanat, and Edele 2017).…”
Section: The Role Of Cultural Identity For Life Satisfaction and Schomentioning
confidence: 82%
See 1 more Smart Citation
“…In contrast, in recent studies from Germany, only cultural minority youths' mainstream identity was associated with school achievement (Schotte, Stanat, and Edele 2017;Hannover et al 2013; Schachner, van de Vijver, and Noack 2018), whereas both heritage and mainstream identity were associated with psychological adjustment, including higher life satisfaction and reduced problem behaviour (Schotte, Stanat, and Edele 2017;Schachner, van de Vijver, and Noack 2018). Some authors have argued that the German school context might hold particularly high assimilative pressures, where students are expected to adapt to the mainstream culture while neglecting their heritage culture (Hannover et al 2013;Bender-Szymanski 2012). Therefore, in an assimilative school context, emphasising mainstream identity might be more important for school success than heritage identity (Makarova and Birman 2016;Schotte, Stanat, and Edele 2017).…”
Section: The Role Of Cultural Identity For Life Satisfaction and Schomentioning
confidence: 82%
“…A large body of acculturation research supports that a high identification with both cultures is related to favourable psychological and school adjustment of cultural minority youth (Nguyen and Benet-Martínez 2013;Makarova and Birman 2016). In contrast, in recent studies from Germany, only cultural minority youths' mainstream identity was associated with school achievement (Schotte, Stanat, and Edele 2017;Hannover et al 2013; Schachner, van de Vijver, and Noack 2018), whereas both heritage and mainstream identity were associated with psychological adjustment, including higher life satisfaction and reduced problem behaviour (Schotte, Stanat, and Edele 2017;Schachner, van de Vijver, and Noack 2018). Some authors have argued that the German school context might hold particularly high assimilative pressures, where students are expected to adapt to the mainstream culture while neglecting their heritage culture (Hannover et al 2013;Bender-Szymanski 2012).…”
Section: The Role Of Cultural Identity For Life Satisfaction and Schomentioning
confidence: 99%
“…Second, the interaction effect shown in our study also emphasizes the importance of cultural values (e.g., vertical collectivism) that are shaped by members of their ethnic group for negatively stereotyped migrant students in the achievement context. Thus, our results add to the discussion of whether adopting the values of one's own culture or one's host culture or a combination of the values of both cultures is most beneficial for migrant students' achievement (e.g., Hannover et al, 2013;Van Laar, Derks, & Ellemers, 2013). However, more research is necessary to explore how vertical collectivism differs from other cultural value orientations (e.g., focusing on values of the host VERTICAL COLLECTIVISM AND STEREOTYPE THREAT 20 culture or both cultures) in stereotype threat situations.…”
Section: Effects On Performancementioning
confidence: 96%
“…He observed that school success for minorities largely depends on the extent to which students corroborates to the value system of the school, which is in line with the dominant/national culture and identity. Different empirical studies show that a higher identification with the nation is associated with higher levels of academic achievement (Baysu et al, 2011;Hannover et al, 2013;Phinney et al, 1997;Trickett and Birman, 2005). However, for minorities, there might be a downside to higher national identification as well.…”
Section: Common Identities and Academic Achievementmentioning
confidence: 99%